2018
DOI: 10.1103/physrevc.98.041901
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy in low transverse momentum dileptons from relativistic heavy-ion collisions

Abstract: The dilepton transverse momentum spectra and invariant mass spectra for low pT < 0.15 GeV/c in Au+Au collisions of different centralities at √ sNN = 200 GeV are studied within the partonhadron-string dynamics (PHSD) transport approach. The PHSD describes the whole evolution of the system on a microscopic basis, incorporates hadronic and partonic degrees-of-freedom, the dynamical hadronization of partons and hadronic rescattering. For dilepton production in p+p, p+A and A+A reactions the PHSD incorporates the l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Indications for dilepton production via photon-photon interactions in hadronic heavy-ion collisions were reported at RHIC and the LHC. The STAR collaboration found an excess with respect to the hadronic expectation of low-p T,ee dielectrons in Au-Au and U-U collisions, which is compatible with calculations for coherent photo-production [1][2][3]6] and which cannot be linked to hadronic sources [7]. The ATLAS collaboration observes photoproduced dimuons in Pb-Pb collisions, which exhibit a centrality dependent broadening effect of their angular pair correlations that seems not to be present in UPC [8,9].…”
Section: Introductionsupporting
confidence: 70%
“…Indications for dilepton production via photon-photon interactions in hadronic heavy-ion collisions were reported at RHIC and the LHC. The STAR collaboration found an excess with respect to the hadronic expectation of low-p T,ee dielectrons in Au-Au and U-U collisions, which is compatible with calculations for coherent photo-production [1][2][3]6] and which cannot be linked to hadronic sources [7]. The ATLAS collaboration observes photoproduced dimuons in Pb-Pb collisions, which exhibit a centrality dependent broadening effect of their angular pair correlations that seems not to be present in UPC [8,9].…”
Section: Introductionsupporting
confidence: 70%
“…It has been shown that the scattering cross sections reproduce the spatial diffusion coefficient of heavy quarks from lQCD calculations and the experimental data on D mesons. Even more, also single electrons as well as dileptons are in agreement with experiment from the beam energy scan energies at RHIC to LHC energies [11,12,[26][27][28].…”
Section: Introductionsupporting
confidence: 82%
“…While thermal radiation (and the hadronic decay "cocktail") dominate the yield for P T >0.2 GeV at all centralities, while the γ γ -fusion gives rise to the pronounced enhancement at P T < 0.15 GeV. Note that a recent transport calculation [81] confirmed that hadronic sources (thermal emission plus cocktail) cannot explain the low-P T excess observed by STAR in peripheral Au-Au collisions. No photoproduction processes were considered in that study.…”
Section: Low Transverse Momentum Dilepton Production In Semicentral Hmentioning
confidence: 78%